2005
DOI: 10.1007/s10704-005-3470-5
|View full text |Cite
|
Sign up to set email alerts
|

Ductile Fracture by Central Bursts in Drawn 2011 Aluminium Wire

Abstract: This paper reports on the application of numerical techniques to predict the initiation and propagation of central burst defects in the wire drawing process. The development and implementation of a suitable failure model into a commercial finite element code, via a user written subroutine, has enabled the occurrence of ductile fracture by central bursting in 2011 Aluminium alloy wire to be successfully analysed. In validating the numerical model, the drawing force, die pressure and occurrence of central burst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…However, the obtained results are compared with those available in the literature. Komori (2003), Alberti et al (1993) and McAllen and Phelan (2005) observed a similar effect for the prediction of central bursting defects. Komori (2003) has investigated the occurrence of central burst defects in copper wire drawing using four kinds of ductile fracture criteria (Gurson 1977;Oyane et al 1980;Cockcroft and Latham 1968;Brozzo et al 1972).…”
Section: Die Geometrysupporting
confidence: 62%
See 2 more Smart Citations
“…However, the obtained results are compared with those available in the literature. Komori (2003), Alberti et al (1993) and McAllen and Phelan (2005) observed a similar effect for the prediction of central bursting defects. Komori (2003) has investigated the occurrence of central burst defects in copper wire drawing using four kinds of ductile fracture criteria (Gurson 1977;Oyane et al 1980;Cockcroft and Latham 1968;Brozzo et al 1972).…”
Section: Die Geometrysupporting
confidence: 62%
“…This author has showed that the material at the center of the cross section is fractured in the analysis using Gurson's fracture criterion, Cockcroft and Latham's fracture criterion, Brozzo et al's fracture criterion and Oyane's fracture criterion. Otherwise, Alberti et al (1993) and McAllen and Phelan (2005) have investigated the formation of central burst defects in drawing of UNI-3571 Aluminium alloy and 2011 Aluminium wire respectively. Their results exhibit a curve dividing the safe and unsafe zones corroborating our present findings.…”
Section: Die Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The study of this problem has attracted the attention since the end of the 19th century (see [1][2][3] for a historical review on this subject). In recent years, the analysis of this process has encompassed different topics such as: assessment of the influence of drawing variables (e.g., drawing velocity, die geometry and heat treatment) on the material response [2][3][4][5][6][7][8] comparison of finite element simulations with analytical results [7][8][9], estimation of the back tension in single [10], and multistep [11][12][13] processes, surface and internal (i.e., chevron) crack formation [14][15][16][17][18][19][20], experimental and numerical evaluation of residual stresses [21][22][23][24][25][26][27], hydrodynamics in the lubricant layer [28,29], wear prediction [30,31], computation of temperature distribution on the wire [30,32,33], strain rate effects in high-speed forming [34], and texture development [35].…”
Section: Introductionmentioning
confidence: 99%
“…Although this type of defect occurs with a small frequency, it is highly insidious because it is usually not visible from the outside and needs special non destructive technique control to be detected. This problem has been addressed in many works using various kinds of local fracture criteria in order to predict the discontinuous chevron shaped cracks formation ( [1][2][3][4][5][6][7][8]). In this paper, thermoelasto-viscoplastic constitutive equations with both non linear isotropic and kinematic hardenings strongly coupled with isotropic ductile damage and thermal effects are used.…”
Section: Introductionmentioning
confidence: 99%